Wireless functional optical imager - Karaca, Serkan. (Thesis (M.S.)-Bogazici University. Institute of Biomedical Engineering, 2005., 2005)
Functional imaging of brain offers the capability to investigate cerebral blood circulation and oxygen metabolism, as well as activity levels of the nervous system. In recent years, technological progress in biophotonics has led to the development of functional near infrared spectroscopy system (fNIRS) which provides non-invasive, rapid and affordable method of monitoring brain oxygenation levels during cognitive activity and even sleep. This M.Sc. thesis is involved with the development of a prototype of a compact wireless optical imaging system (WFOI). WFOI is composed of a probe that houses inexpensive photodiode detectors (PD), LED working in the near infrared spectrum, a LED driver circuit for constant current supply, a data acquisition unit composed of a microcontroller such as a PIC16F877, a data transmission unit, exploiting the RF communication technology and a PC based software for data logging and analysis. WFOI is designed to be used in sleep apnea studies as well as in pediatric research especially for hyperactive children.
Keywords: Near infrared spectroscopy.; Brain -- Imaging.; Nervous system -- Imaging.; Telemeter.